Implementation Status of Journalist Code of Conduct in Nepali Weekly Newspapers - Bidari, Shantaram (RR Interdisciplinary Journal, 2024)
Societal responsibility needs ethical journalism. While journalists engage in advocacy of rights, they must also fulfill their own part of the obligation. However, in Nepali journalism, especially in weeklies, the core ethics and principles of ethical journalism are very readily abandoned. They are charged with violating the Journalist Code of Conduct. To increase the credibility of the media sector, it is essential that the principles of ethics such as truth, impartiality, balance, and factuality are adhered to in a serious manner. Nonetheless, the recent trends suggest the opposite, and hence there is growing public concern about the role of the media. This research examines the usage of the Journalist Code of Conduct by Nepali weekly newspapers. Despite increasing importance being attached to ethical journalism, instabilities in following these principles are felt. The research aims to establish the current status of the usage of the code and how issues in enforcement arise. The research employed a mixed-method approach, i.e., literature review, interviews with reporters, and content analysis of the chosen weekly newspapers. This helped to provide an overview of ethical practice and concerns. Findings show that while some weekly newspapers adhere to ethical standards, others do not, and there are very large gaps in their adherence to the code. Substantial issues are poor media literacy, poor editorial oversight, and external pressures. The study concludes with the recommendation for the improvement of compliance to the code, such as more intensive training of reporters, more stringent editorial guidelines, and more importance on ethical journalism. Overcoming the issues can make Nepali media more believable and socially accountable.